Analisis Biaya Kualitas untuk Mencapai Zero Defect pada UMKM Mie Wahyu SPJ - Tiara Ayu Andini; Insyirah Putikadea (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
This study aims to analyze the cost of quality at Mie Wahyu UMKM to achieve zero defects. The background of this study is the high number of defective products experienced by MSMEs during September-December 2023. The purpose of the quality cost analysis is to determine the amount of quality costs and to be useful as a basis for further quality improvements so that there are no more defective products (zero defects). The method used in this study is a case study with sources from observations, interviews, and documentation at the Mie Wahyu UMKM production site. Furthermore, the data collected was processed and analyzed using the quality cost method. The results of the study showed that during the year from September to December, the average total cost of quality per sale was 6,5%. This means that the total cost of quality per sale is still above the optimal figure of 2.5% per actual sale. The high cost of quality proves that there are still customer complaints, so that Mie Wahyu UMKM must improve quality by carrying out regular maintenance, periodic inspections, employee training, etc. in order to achieve zero defects.